2022
DOI: 10.1016/j.ijscr.2021.106719
|View full text |Cite
|
Sign up to set email alerts
|

A case of spontaneous thoracolumbar epidural hematoma in Covid-19 pneumonia

Abstract: Introduction and importance Covid-19 is an important disease that still occupies our agenda, and as time passes, we have been observing its extrapulmonary manifestations. In this study, we presented a case of spontaneous thoracolumbar epidural hematoma, which we could not attribute to any cause other than Covid-19. Case presentation We presented a 55-year-old female patient whose etiology could not be found to be compatible with the literature. In the formation of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…To our knowledge, this case is the first report of a chiropractor identifying SEH. As the patient had no specific risk factors for SEH and diclofenac is not associated with SEH to our knowledge [14], it seems possible given other similar recent studies [5][6][7][8] that his COVID-19 illness could have been a predisposing factor for SEH.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…To our knowledge, this case is the first report of a chiropractor identifying SEH. As the patient had no specific risk factors for SEH and diclofenac is not associated with SEH to our knowledge [14], it seems possible given other similar recent studies [5][6][7][8] that his COVID-19 illness could have been a predisposing factor for SEH.…”
Section: Discussionmentioning
confidence: 61%
“…According to a search of PubMed and Google Scholar on November 18, 2022, we identified four previously published cases of spontaneous SEH in patients following COVID-19 infection [5][6][7][8]. Several mechanisms have been suggested to explain these events, including venous thromboembolism, disseminated intravascular coagulation, increased pressure in the epidural venous plexus, and vasculitis [5][6][7], however, there is no clear unifying pathophysiological explanation. In addition, larger studies have identified an association between COVID-19 and other conditions involving bleeding such as intracranial hemorrhage and spontaneous muscle hematoma [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lim et al 18 reported a cervical spine spontaneous epidural hematoma in a COVID‐19‐infected woman treated conservatively. Zubeyde et al 5 reported another epidural hematoma in an older woman positive for SARS‐CoV‐2 virus that underwent laminectomy and hematoma evacuation.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 Myelitis, neuropathy, spinal cord dysfunction, and hemorrhagic lesions are amongst the reported spinal manifestations of SARS‐CoV‐2. 2 , 3 , 4 , 5 …”
Section: Introductionmentioning
confidence: 99%